Cost-benefit analysis of using cold thermal energy storage systems in building applications - Rismanchi, Behzad; Saidur, Rahman; Masjuki, Haji Hassan; Mahlia, Teuku Meurah Indra (2012)
This study attempts to predict the potential cost savings of employing ice thermal storage (ITS) systems in the office buildings cooling application in Malaysia over the next 20 years. During the past decades, huge amount of daytime peak power has been shifted to the off-peak hours by using cool thermal energy storage (CTES) systems around the world. However, the contribution of CTES systems in Malaysia is still small in comparison with its potential. This study is conducted for three different scenarios of retrofitting 10, 25 and 50 of the existing conventional AC systems with new ITS systems. The overall results show that the full storage strategy can reduce the annual costs of the air conditioning system up to 35 percent while this reduction is limited to around 8 percent for load leveling strategy.